The Impact of Privatization and Commercialization in Nigeria - Stephen, Chukwuma Chukwudumebi; Omokhudu, Odiwo Williams; Anthony, Kifordu Anyibuofu (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
This paper examined the activities/policies of privatization and commercialization of public enterprises in Nigeria and how they have affected the development of the Nation. Although, some of the problems facing public- owned enterprise were examined as well. It looked at the pressure on the International Monetary Fund (IMF) to fully implement the structural adjustment program that leads to massive deregulation, privatization, and commercialization of public owned enterprises. In addition, it looked at the merits if any, of privatization and commercialization through extensive theoretical review of the performance of the private enterprise in Nigeria. Theories, rationale, and challenges of privatization and commercialization were addressed. The conclusion was that privatization is a good policy measure, which must be pursued with vigor, truth, sincerity, and transparencies even though the government is using such policies to foster a new division of labor between the public and private sectors in a bid to order, increase the efficiency and contribution to the development of both sectors. Privatization and commercialization in Nigeria will be a mirage unless institutional reforms take place. The government should create an environment favorable for private economic activity. This can be done by showing zero tolerance for corruption, nepotism, and misuse of public funds and property by both government and non-government officials.